Reduced NK Cell Cytotoxicity by Papillomatosis-Derived TGF-β Contributing to Low-Risk HPV Persistence in JORRP Patients - Wu, Xunyao; Xiao, Yang; Guo, Dan; Zhang, Zixin; Liu, Meiyu (Frontiers in Immunology, 2022)
The role of natural killer (NK) cells in juvenile-onset recurrent respiratory papillomatosis (JORRP) patients remains elusive. In this study, we find increased NK cell percentage, particularly CD11b-CD27- (DN) subsets in peripheral blood of JORRP patients and associated with disease activity. RNA sequencing shows a downregulated “natural killer cell-mediated cytotoxicity” feature in JORRP tumors. We also find impaired cytotoxic capacity and lower expression of NK cell-activating receptors including NKp30 and NKp46. Higher transforming growth factor-beta 1 (TGF-β1) is found both in plasma and tumor tissues of JORRP, and anti-TGF-β1 antibody could restore NK cell cytolytic activity and upregulate NKp30 and NKG2D expression. Also, we find a significantly higher Chemokine receptor type 6 (CXCR6) on NK cells in tumors compared with that in peripheral blood. Finally, RT-PCR analysis show that both HPV6-E6-E7 and HPV11-E6-E7 overexpression leads to higher TGFB1 expression compared with control SNU-1076 cell line, and higher CXCR6 expression is detected on NK coculture with HPV11-E6-E7-overexpressing cells. In conclusion, we demonstrate that TGF-β1 by papillomatosis leads to decreased NK cell cytotoxicity through downregulating NK cell-activating receptors in JORRP patients.